KOMODIFIKASI AGAMA MELALUI IKLAN TELEVISI (STUDI KASUS IKLAN TELEVISI BERLABEL HALAL) - Agustian Bhaskoro Abimana Aryasatya (Jurnal Pustaka Ilmiah, 2019)
Religion in the present era is inseparable from commodification. The change in the paradigm of religion which regulates human life delivered through tauziah-tauziah in pengajian or mosque is now beginning to shift to the culture of commodification through advertising on television media. This shift began to penetrate the media used in understanding the teachings of Islam which are more acceptable to the people of the present era by using halal labels in them. This article discusses the commodification of religion through television advertising case studies on halal-labeled advertisements. The method used is a library research that will be described narratively. The results of the discussion of this article are the existence of new phenomena in expressing Islamic values in the lives of individuals in the current technological era. The presence of Islam that is accepted taken for grated, namely an individual prefers what is in accordance with him and in accordance with his religion. So what is not appropriate will be considered not as the identity of the individual. Besides that there is destabilized identify, that is religion is used as an alternative to create a new identity. In addition, these signs have led to the concept of symbolic capital, a position where an identity can shape the position of an individual in his social class Keywords: Commodification of Religion, Islam, Halal Labeled Advertising, Television Media